Step-by-step explanation:
given point [tex]C=(-6,0)[/tex] ,[tex]A=(4,-2)[/tex] and [tex]T=(5,3)[/tex]
Distance between any two points [tex]p1=(x_{1},y_{1})[/tex] and [tex]p2=(x_{2},y_{2})[/tex] is [tex]\sqrt{(y_{2}-y_{1})^{2} +(x_{2}-x_{1})^{2}}[/tex]
Distance between the points [tex]C[/tex] and [tex]A[/tex]=[tex]ca=[/tex][tex]\sqrt{(0-(-2))^2+(-6-4)^2}=\sqrt{104}[/tex]
Distance between the points [tex]A[/tex] and [tex]T[/tex]=[tex]at=[/tex][tex]\sqrt{(-2-(3))^2+(4-5)^2}=\sqrt{26}[/tex]
Distance between the points [tex]T[/tex] and [tex]C[/tex]=[tex]tc=[/tex][tex]\sqrt{(3-0)^2+(5-(-6))^2}=\sqrt{130}[/tex]
calculate [tex]ca^{2}+at^{2}=104+26=130[/tex]
calculate [tex]tc^{2}[/tex][tex]=130[/tex]
So,[tex]ca^{2}+at^{2}=tc^{2}[/tex]
Since,sum of squares of two sides is equal square of the third side,using pythagoras theorem
The triangle is a right angled triangle.